The DIME project: Background, status and future perspectives of a user driven recording scheme for metal detector finds as an example of participatory heritage - Dobat, Andres Siegfried; Christiansen, Torben Trier; Jessen, Mads Dengsø; Henriksen, Mogens Bo; Jensen, Peter; Laursen, Stine Vestergaard; Ruhe, Rikke; Holst, Mads Kähler; Arntsen, Freddy (Danish Journal of Archaeology, 2019)
In september 2018, the DIME portal was officially launched to facilitate the user driven recording of metal detector finds produced by members of the public. The concrete and operational aim of DIME is to provide a portal for the registering and hence safeguarding of the increasing number of metal detector finds and to make them accessible for the general public and for research. The more overarching vision behind the DIME project is to realise the potential of recreational metal detecting as a medium to implement an inclusive and democratic approach to heritage management in Denmark and to advance the incorporation of principles of citizen science and crowdsourcing in museum practice. This article intends to present the background of the DIME portal’s development, its basic functionalities and their technological underpinning as well as the overarching vision behind DIME.